2016
DOI: 10.3389/fevo.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

Kin Signatures Learned in the Egg? Red-Backed Fairy-Wren Songs Are Similar to Their Mother's In-Nest Calls and Songs

Abstract: Many vocal animals recognize kin using vocal cues, in territorial contexts and in rearing young, but little is known about the developmental and evolutionary mechanisms that produce vocal kin recognition systems. In the cooperatively breeding red-backed fairy-wren (Malurus melanocephalus), females give specific "in-nest calls" while incubating their eggs. Elements from these calls are incorporated into chicks' begging calls, and appear to be used by parents for recognition. This is likely a result of an embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In practice, it is extremely difficult to rule out prior association in most field studies, even in cross-fostering experiments where there is often a period of association between parents and offspring prior to separation (e.g., Hatchwell et al, 2001). Kin recognition cues may even develop during gestation (e.g., Hepper, 1987) or incubation (e.g., Colombelli-Négrel et al, 2012;Dowling et al, 2016). Secondly, familiarity is generally assumed to result in dichotomous classification of conspecifics into familiar (kin) and unfamiliar (non-kin) individuals, while cue-template similarity under phenotype-matching is assumed to be continuous.…”
Section: Familiarity Vs Phenotype Matchingmentioning
confidence: 99%
“…In practice, it is extremely difficult to rule out prior association in most field studies, even in cross-fostering experiments where there is often a period of association between parents and offspring prior to separation (e.g., Hatchwell et al, 2001). Kin recognition cues may even develop during gestation (e.g., Hepper, 1987) or incubation (e.g., Colombelli-Négrel et al, 2012;Dowling et al, 2016). Secondly, familiarity is generally assumed to result in dichotomous classification of conspecifics into familiar (kin) and unfamiliar (non-kin) individuals, while cue-template similarity under phenotype-matching is assumed to be continuous.…”
Section: Familiarity Vs Phenotype Matchingmentioning
confidence: 99%
“…Accordingly, a recent study in superb fairy-wrens ( Malurus cyaneus ) suggested that embryos responded to males’ (but not females’) songs, as indicated by changes in embryonic heart rate 6 . Likewise, in the closely-related red-backed fairy-wren ( M. melanocephalus ), a correlational study found that individuals’ adult song partly resembled their mother’s song, which in turn had similarities with her incubation call 16 . This raises the possibility that prenatal incubation call exposure might, indeed, bias individuals towards learning particular songs later in life, although this remains to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…They sometimes exhibit specific morphological adaptations to do so (e.g., teeth in caecilian embryos: Wake, ); Kill siblings to reduce competition for food —for example, invertebrates (Harrath, Sluys, Zghal, & Tekaya, ; Thomsen, Collin, & Carrillo‐Baltodano, ) and sharks (Gilmore, ); Regulate amniotic fluid volume by drinking —Cordero et al. () interpret sucking behavior pre‐birth as nonfunctional, but this behavior plausibly adjusts fluid volumes among compartments of the oviductal package (i.e., moving fluid from the amniotic sac to the allantois), thereby enhancing offspring viability (El‐Haddad, Desai, Gayle, & Ross, ); “Eavesdrop” on developmental rates of siblings —enabling embryos to hatch synchronously with the rest of the clutch, thereby gaining fitness benefits associated with concurrent emergence from the nest, predator satiation, and so on (McGlashan, Spencer, & Old, ); Identify the optimal time to hatch based on external cues —including diel cycles (Radder & Shine, ), drought stress (Newman, ), and imminent predation (Warkentin, ); Learn dialect of local songs —by listening to the mother's vocal repertoire while they are still inside the egg (in birds: Dowling, Colombelli‐Négrel, & Webster, ); Vocalize within the egg shortly before hatching —to induce hatching in siblings and stimulate the adult female to open the nest (in crocodilians: Vergne & Mathevon, ) or to exhibit other parenting behaviors (in birds: Bolhuis & van Kampen, ; Reed & Clark, ; Rumpf & Nichelmann, ); and Reposition within the egg —to behaviorally thermoregulate (reptiles: Du et al., ; birds: Li et al., ; Marasco & Spencer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Learn dialect of local songs —by listening to the mother's vocal repertoire while they are still inside the egg (in birds: Dowling, Colombelli‐Négrel, & Webster, );…”
Section: Introductionmentioning
confidence: 99%